Firms' Investment and Savings in Latin America: Stylized Facts from the Enterprise Survey - Enrique Kawamura; Lucas Ronconi (Inter-American Development Bank (IDB), 2015)
This paper describes the share of investment in fixed capital and working capital financed by retained earnings using a harmonized dataset from the World Bank Enterprise Survey. The sample includes firms across countries in Latin America and the Caribbean. Descriptive statistics are presented for the share of purchases of fixed assets financed with internal funds or retained earnings, the share of working capital financed with internal funds, the ratio between internal funds used for purchasing fixed assets and sales, and annual purchases of fixed assets (as a proportion of annual sales). Also presented are stylized facts exploring how these variables differ by country, firm size, firm age, registration, sector of activity, and ownership. It is found that internal funds are extensively used to finance both purchases of fixed assets and working capital, particularly by smaller firms located in countries with less developed financial markets. Investment in fixed assets represents about 7. 5 percent of sales in the region and is significantly higher among larger and registered firms.
hdl:11319/7349
Keywords: D22; G32; E21; E22; 330; Investment financing; Retained earnings